ARKHANGELSK URBAN AGGLOMERATION. MINI-PORTRAITS OF SETTLEMENTS (BY THE MATERIALS OF TRAVEL OBSERVATIONS) - I. A. Soloviev; V. V. Chikhichin; E. I. Ovsyannikov; J. F. Zolnikova (Наука. Инновации. Технологии)
Introduction. In the article, on the basis of travel observations carried out during the expedition to study the demographic development of the Arkhangelsk urban agglomeration, general geographical mini-portraits of the cities of Arkhangelsk, Severodvinsk, Novodvinsk and the village of Lomonosovo were compiled. Materials and methods. The key research method is visual observation and a survey of the local population. The work also used official statistics on the number of residents of settlements that are part of the Arkhangelsk urban agglomeration. Results and discussion. The article describes some features of the geographical location, nature, population, economy, planning structure of settlements, the nature of their development, improvement of urban spaces, etc. There is a feeling of depressiveness in the settlements of the Arkhangelsk urban agglomeration, which is expressed in a large number of dilapidated and dilapidated housing, and the lack of amenities in courtyards and sidewalks. Conclusions The exception is the showcase central parts of cities.